1984
DOI: 10.1136/gut.25.7.718
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indomethacin on basal and histamine stimulated human gastric acid secretion.

Abstract: SUMMARY The effect of acute administration of indomethacin over 24 hours on basal and histamine stimulated gastric acid secretion was evaluated in seven normal male volunteers. Augmented histamine tests (0.015 mg/kg/h) infused with the antihistamine diphenhydramine hydrochloride (25 mg/h) were performed before and after pretreatment with indomethacin or matching placebo capsules. The dose of indomethacin was 75 mg (sustained release capsules) taken 12 and 24 hours before and 50 mg taken one hour before a two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 12 publications
4
26
0
Order By: Relevance
“…We have shown that aspirin potentiates secretagogue-stimulated acid secretion in PC, as previously demonstrated for NSAIDs in vivo and in vitro (4)(5)(6)(7)(8). Several possibilities exist concerning the mechanisms by which aspirin affects stimulussecretion coupling and thereby potentiates PC function.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We have shown that aspirin potentiates secretagogue-stimulated acid secretion in PC, as previously demonstrated for NSAIDs in vivo and in vitro (4)(5)(6)(7)(8). Several possibilities exist concerning the mechanisms by which aspirin affects stimulussecretion coupling and thereby potentiates PC function.…”
Section: Discussionmentioning
confidence: 65%
“…7). The decrease in PGE2 levels induced by aspirin could augment acid secretion in PC as we observed in the chambered frog gastric mucosa (37) and for indomethacin in vivo (5). However, in PC basal acid secretion was unaffected by this degree of reduction in PGE2 levels.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This was supported by indirect studies employing different non-steroidal antiinflammatory agents (NSAIDs) as inhibitors of PGs generation, and by direct measurement of PGs production in the gastric juice or mucosal homogenates [2,3]. The finding that PGs may be synthesized by the gastric mucosa in response to secretory stimuli and exhibit an inhibitory action on gastric secretion suggests that endogenous PGs may locally modulate acid production by a negative feed-back mechanism.…”
Section: Introductionmentioning
confidence: 97%
“…In a first series four tests were made in random order in each of 9 healthy male subjects with an aver age age of 31 (range [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] years and normal body weight. Plasma concentrations of somatostatin and gastrin, luminal somatostatinlike immunoreactivity.…”
Section: Series With Vagal Stimulationmentioning
confidence: 99%